Expression of the yeast PHR1 gene is induced by DNA-damaging agents. - Sebastian, J (1990)
The PHR1 gene of Saccharomyces cerevisiae encodes a photolyase which repairs specifically and exclusively pyrimidine dimers, the most frequent lesions induced in DNA by far-UV radiation. We have asked whether expression of PHR1 is modulated in response to UV-induced DNA damage and to DNA-damaging agents that induce lesions structurally dissimilar to pyrimidine dimers. Using a PHR1-lacZ fusion gene in which expression of beta-galactosidase is regulated by PHR1 5' regulatory elements, we found that exposure of cells to 254-nm light, 4-nitroquinoline-N-oxide, methyl methanesulfonate, and N-methyl-N'-nitro-N-nitrosoguanidine induced synthesis of increased amounts of fusion protein. In contrast to these DNA-damaging agents, neither heat shock nor exposure to photoreactivating light elicited a response. Induction by far-UV radiation was evident both when the fusion gene was carried on a multicopy plasmid and when it replaced the endogenous chromosomal copy of PHR1, and it was accompanied by an increase in the steady-state concentration of PHR1-lacZ mRNA. Northern (RNA) blot analysis of PHR1 mRNA encoded by the chromosomal locus was consistent with either enhanced transcription of PHR1 after DNA damage or stabilization of the transcripts. Neither the intact PHR1 or RAD2 gene was required for induction. Comparison of the region of PHR1 implicated in regulation of its expression with other damage-inducible genes from yeast cells revealed a common conserved sequence that is present in the PHR1, RAD2, and RNR2 genes and is required for damage inducibility of the latter two genes. These sequences may constitute elements of a damage-responsive regulon in S. cerevisiae.